2011
DOI: 10.1016/j.amepre.2011.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Public School Districts to Adopt Sun Protection Policies

Abstract: Background In 2002, CDC recommended that the nation’s schools establish policies that reduce sun exposure to decrease students’ risk of skin cancer. Purpose A program to convince public school districts to adopt such a policy was evaluated. Design RCT. Setting/Participants Public school districts in Colorado (n=56) and Southern California (n=56). Intervention Policy information, tools and technical assistance were provided through printed materials, a website, meetings with administrators, and presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Of the 12 studies that assessed adoption , four found a significant within group difference [ 22 , 24 , 26 , 40 ] and two found significant between group differences in adoption rates with the intervention group having higher rates than the comparison [ 39 , 47 ]; four additional studies found an increase in adoption following the capacity-building intervention without testing for significance [ 21 , 25 , 46 , 48 ]. Findings were mixed, however, as four studies found non-significant group differences in adoption rates [ 24 , 26 , 44 , 49 ]. Of the 11 studies that assessed effects on the extent or fidelity of implementation , all but one reported that capacity building had a positive effect.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 studies that assessed adoption , four found a significant within group difference [ 22 , 24 , 26 , 40 ] and two found significant between group differences in adoption rates with the intervention group having higher rates than the comparison [ 39 , 47 ]; four additional studies found an increase in adoption following the capacity-building intervention without testing for significance [ 21 , 25 , 46 , 48 ]. Findings were mixed, however, as four studies found non-significant group differences in adoption rates [ 24 , 26 , 44 , 49 ]. Of the 11 studies that assessed effects on the extent or fidelity of implementation , all but one reported that capacity building had a positive effect.…”
Section: Resultsmentioning
confidence: 99%
“…These types of interventions often take place in school settings and can involve constructing shade structures. 18, 51 Because schools often do not have policies that facilitate sun safety, built environment and policy interventions in school settings could have a major impact on skin cancer outcomes. 52 Policies at workplaces—particularly those involving outdoor work such as ski slopes or zoos—were targeted in relatively few interventions.…”
Section: Discussionmentioning
confidence: 99%
“…12, 17 Examining multiple types of environmental manipulations promotes understanding of these initiatives within the context of skin cancer behavioral change interventions. 1820…”
Section: Introductionmentioning
confidence: 99%
“…Given the limited effectiveness of directly intervening with individuals, an alternative approach may be to address policy and environmental features of resorts. Studies of school and occupational sun safety have found that senior managers can be convinced to adopt sun protection policies (Buller, Walkosz, Buller, & Wallis, 2015, December; Buller, Reynolds, et al, 2011), which could overcome detrimental effects of management turnover or varied commitment of managers to sun safety. Encouraging resorts to provide shade structure also may attract vacationers to use shaded areas (Dobbinson et al, 2014; Dobbinson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%